1988
DOI: 10.2105/ajph.78.12.1577
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the distribution of physicians in rural areas of Minnesota, 1965-85.

Abstract: PUBLIC HEALTH BRIEFS posttest counseling in this study, diverse forms of information and social support were given by the nurses who maintained contact with the participants. Testing was voluntary, with informed consent and under the strict condition of confidentiality. Because ethical and practical considerations prohibit experimenting with the factors mentioned above, their individual contribution to the effect of testing cannot be distinguished. ACKNOWLEDGMENTSThe authors wish to acknowledge with appreciati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…As health care costs continue to escalate, many farm families and rural employers are finding health insurance premium costs to be prohibitive (Baldwin, 1986). Efforts to reduce costs are causing some rural hospitals to close or reduce their services, and many rural communities are finding it difficult to attract physicians, in part because of economic factors, but also because it is increasingly difficult to practice medicine in solo practices (Dennis, 1988;Cordes, 1989). This article reports the findings of a study designed to evaluate the magnitude of this problem in Minnesota.…”
mentioning
confidence: 99%
“…As health care costs continue to escalate, many farm families and rural employers are finding health insurance premium costs to be prohibitive (Baldwin, 1986). Efforts to reduce costs are causing some rural hospitals to close or reduce their services, and many rural communities are finding it difficult to attract physicians, in part because of economic factors, but also because it is increasingly difficult to practice medicine in solo practices (Dennis, 1988;Cordes, 1989). This article reports the findings of a study designed to evaluate the magnitude of this problem in Minnesota.…”
mentioning
confidence: 99%
“…As the pool of physicians continues to expand, they maintained, the competitive pressures force the newcomers to increasingly locate outside metropolitan areas (Newhouse et al, 1982). Several recent studies have acknowledged the general predictions of "diffusion theorists" but have disagreed that these forces will alleviate all geographic imbalances (Cordes & Eiseles, 1986;Dennis, 1988;Fruen & Cantwell, 1982;Hynes & Givner, 1983;Kindig & Movassaghi, 198% Wright, 1985).…”
mentioning
confidence: 99%
“…In 1987, a National Governors' Association survey found that access to maternal and child health services was a problem in rural areas in 35 states, compared to urban/suburban areas, for which only three states reported a problem (Bernstein, Kolimaga, and Neuschler 1988b). The physician-population ratio decreased by 2 percent for primary care physicians and by 11 percent for family practitioners in non-MSA counties in Minnesota between 1965 and (Dennis 1988). This occurred despite an overall increase in the number of physicians in Minnesota.…”
Section: Rural Health Care Providersmentioning
confidence: 99%